A concerning trend in geriatric pharmacy that merits evidence-based intervention. Issue 4 (9th June 2022) - Hughes, Hunter Merritt; Nizami, Hamasah; Polanco, Juan Sebastian; Poulson, Jessica; Cai, Alice; Mittal, Rea; Su, Lilly; Jain, Pranjal; Jain, Rohit
Abstract: The effects of polypharmacy on geriatric populations are an emerging concern that merits more exploration. The primary goal of this review was to evaluate the current body of knowledge on polypharmacy and explore the preventive and corrective measures to avoid negative outcomes. Even if a medication has an appropriate indication, polypharmacy in the geriatric population is associated with an increased risk of drug-drug or drug-condition interactions. Recent efforts to prevent polypharmacy include the development of interprofessional teams in clinics dedicated to medication review and reconciliation, deprescription plans aimed to safely discontinue potentially inappropriate medications, and inpatient screening tools that provide prescribing recommendations. In conclusion, polypharmacy affects a high percentage of the geriatric population. Current efforts to address and prevent polypharmacy are ongoing but have not been widely adopted.